PENGARUH KOMPENSASI FINANSIAL, BEBAN KERJA DAN LINGKUNGAN KERJA TERHADAP TURNOVER INTENTION KARYAWAN PADA HARPER HOTEL KUTA - I Putu Andreas Adi Astawa; I Ketut Sutapa (Universitas Triatma Mulya, 2020)
This research is in the background of the phenomenon of employee turnover or high labour turnover in tourism sector especially employees at Harper Hotel Kuta. The research aims to analyse and prove the impact of financial compensation, workload and the working environment on turnover intention. This research uses a descriptive method with a quantitative approach. The technique of sample used is with nonprobability sampling technique, namely by sampling saturated. Number of respondents used 65 employees Harper Hotel Kuta. Analysis of multiple linear regression using SPSS software version 23. Acquired regression equation: Y = 30.664-0, 466X1 + 0, 600X2 – 0, 232X3. The results of this study show that; First, financial compensation negatively affects the turnover intention employees of Harper Hotel Kuta. Secondly, the workload has a positive effect on the turnover of intention employees at Harper Hotel Kuta. Third, the work environment negatively affects the turnover intention employees of Harper Hotel Kuta. Fourth, the magnitude of influence donated by financial compensation, the workload and the working environment of the turnover intention employees of Harper Hotel Kuta is 52.3%. Some of the suggestions that can be conveyed from this study include; Empower employee cooperatives to support the welfare of employees, see the suitability of job description and job spesification, conduct routine maintenance of tools and machines and ensure the safety of employees in doing work.